1997
DOI: 10.1136/jme.23.4.207
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of CPR decision-making by elderly patients.

Abstract: Traditionally clinicians have determined their patients' resuscitation status without consultation. This has been condemned as morally indefensible in cases where notfor resuscitation (NFR) orders are based on quality of life considerations and when the patient's true wishes are not known. Such instances would encompass most resuscitation decisions in elderly patients.Having previously involved patients in CPR decisionmaking, we chose formally to explore the reasons behind the choices made.Although the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…37 65 Some acutely ill hospitalised patients who have been asked what they think about DNR orders have been at increased risk for depression or acute stressors that might impair their judgment. 79 Family members often misinterpret the wishes of elderly relatives. 58 64 80 On one hand, a study showed relatives underestimate the patients' preferences for CPR.…”
Section: Studies Of Patient and Family Attitudes Toward Dnr Ordersmentioning
confidence: 99%
“…37 65 Some acutely ill hospitalised patients who have been asked what they think about DNR orders have been at increased risk for depression or acute stressors that might impair their judgment. 79 Family members often misinterpret the wishes of elderly relatives. 58 64 80 On one hand, a study showed relatives underestimate the patients' preferences for CPR.…”
Section: Studies Of Patient and Family Attitudes Toward Dnr Ordersmentioning
confidence: 99%
“…15 Usually patients wish to participate in the decision making, 16 but some patients may misunderstand discussions on resuscitation, and, at worst, anxiety may be provoked in others. 17 According to several studies, family members, physicians, and nurses cannot predict patients' treatment choices with sufficient accuracy. 18 In addition patients do not necessarily consider autonomy very important.…”
mentioning
confidence: 99%
“…Although many patients report satisfaction with the DNR discussion [2], a minority of patients (0-40%) experience negative reactions to discussions about life-sustaining treatments, including "puzzlement," "anxiety," "sadness," "hopelessness," and a feeling that the discussion itself was "cruel and insensitive" [8]. Other studies give analogous results: Sayers et al report distress in patients 1 week after the DNR discussion [16] and Singer et al report that patients may consider life-sustaining treatment discussions a private matter that it would be more appropriate for them to have with members of their family than with health care providers [17]. A 1998 study of 33 subjects reports that 6% of the participants did not want the discussion, 3% felt pressured, and 7% did not agree with the conclusion that they should have a DNR order [9].…”
Section: Introductionmentioning
confidence: 80%